Strengthening the green economy for developing countries through the implementation of Maqasid Syariah - Harjoni; Rijal, Syamsul; Jailani, Munawwar Rizki; Yulia (Penerbit Universiti Kebangsaan Malaysia, 2024)
Economic development that does not follow the rules of its existence can be detrimental to the living ecosystem. Many efforts have been made throughout the world to eliminate these negative impacts. Recently, religious concepts related to green economics have received attention again, including Islamic views on this matter. The problem formulation in this article is the concept of Islam in sustainable development. So this research aims to find the ideal concept of Islam in sustainable development. The research method used is a qualitative descriptive method with a library study type of research, where the researcher relies on various literature related to the study topic. The research results show that Islam has the ideals concept of sustainable development. At least there are basic principles in supporting sustainable development with the concept of a green economy, namely the application of fiqh al-bi’ah (fiqh environment) based on values guided by maqashid sharia for managing sharia resources in the economy.